Anti-Inflammatory Effect of Vanillin Protects the Stomach against Ulcer Formation - Ciciliato, Murilo Piologo [UNESP]; Souza, Matheus Chiaradia de [UNESP]; Tarran, Carolina Mendes [UNESP]; Castilho, Ana Laura Tironi de[UNESP]; Vieira, Ana Júlia [UNESP]; Rozza, Ariane Leite [UNESP] (MDPI, 2022)
Gastric ulcer is one of the most frequent gastrointestinal disorders, and there is an increasing search for natural products that can heal ulcers and avoid their recurrence. We aimed to evaluate the gastroprotective activity of vanillin, including the investigation of anti-inflammatory activity and the modulation of gene expression. Wistar rats were orally treated with vehicle, carbenoxolone, or vanillin (25, 50, or 100 mg/kg) and orally received absolute ethanol to develop gastric ulcers. We analyzed the ulcer area, conducted histological analysis, and measured the levels of the inflammatory cytokines TNF-α, IL-6, IL-1β, and IFN-γ, and anti-inflammatory cytokine IL-10 by ELISA. We analyzed mRNA expression for NF-κB, TNF-α, and Il-10. We measured NOx levels using the Griess reaction. Our results showed similar gastroprotection for the three doses. Vanillin increased mucus production and preserved gastric mucosa integrity. The gastroprotective effect was linked to anti-inflammatory activity as a result of decreasing the levels of TNF-α, IL-6, IL-1β, and IFN-γ and increasing IL-10 levels. Vanillin downregulated the mRNA expression of NF-κB and TNF-α, upregulated the mRNA expression of Il-10, and increased NOx levels in the stomach. The gastroprotective activity of vanillin is related to the maintenance of gastric mucus and the local inflammatory response modulation.
Keywords: ELISA; IFN-γ; IL-1β; inflammation; NF-κB; NO; qPCR; stomach; TNF-α; vanillin